Evaluatıon of lamınate veneer preparatıons with 3d systems - Oztoprak, Orhan (My University, 2016)
LAMİNA VENER PREPARASYONLARININ ÜÇ BOYUTLU OLARAK DEĞERLENDİRİLMESİ ÖZET Amaç: Laminate Veneer preparasyonlarının kesim derinliğinin Yüksek Lisans Protez öğrencisi (YPÖ) ile Protez Uzmanı (PU) arasındaki farkın 3 boyutlu tarayıcı ile değerlendirilmesi. Yöntem: YPÖ ile PU arasındaki kaldırılan dokunun hacmini ölçmek amacıyla yirmi çekilmiş diş rastgele 2 gruba ayrıldı.1mm lik insizal indirgeme derin chamfer frezi ile gerçekleştirildi. Bukkal ve insizal indirgeme için 0.5mm ‘lik rehber frezi kullanıldı. Dişler 100 µm detay seviyesiyle Üc boyutlu tarayıcı ile tarandı. Dişler insizal, orta ve servikal olmak üzere bölümlere ayrıldı ve hazırlanmamış dişte her bir bölümün 5 noktası rastgele seçilerek taranıp kesim sonrası tekrar taranarak üst üste çakıştırıldı. Bu işlem sonrasında 15 noktada kaldırılan diş dokusu hesaplandı. Bu veriler 3 boyutlu tarama olan Magics (Materialise NV, Belgium)‘te açılarak farklar hesaplandı. Bulgular: PU’ nun ortalama değerleri insizal üçlüde 0.328 +0.045mm, orta üçlüde 0.375 +0.097 mm ve servikal üçlüde 0.471 +0.07mm bulundu. YPÖ nün ortalama değerleri insizal üçlüde 0.323 +0.056mm, orta üçlüde 0.403 +0.083mm ve servikal üçlüde 0.462 +0.075mm bulundu. Sonuç: Yapılan değerlendirmede iki grup arasında istatistiksel olarak anlamlı bir fark bulunmamıştır (p<0.05) . Bu verilere dayanarak, YPÖ ve PU’nun depth guide frezi kullanması ile aynı kesim derinliği ve hassasiyetinin elde edebileceği gösterilmiştir. Seramik vener, Üç Boyutlu tarayıcı, rehber frez.

Purpose: To evaluate difference between a trained professional prosthodontist (PP) and a postgraduate prosthodontics student (PPS) in the preparation depth of laminate veneers by scanning the tooth with a 3D scanner before and after the preparation. Material and Method: Twenty extracted human maxillary central incisors were randomly allocated into two groups to test the volume of tooth removal between the PP and PPS. A 0.5 mm depth guide bur was used in the preparation design for facial and incisal reduction and a 1 mm incisal reduction was performed with a deep chamfer finish without palatal chamfer. The teeth were scanned using Scanitorthodontics program at a detail level of 100 microns. Measurements of the teeth were performed before the preparation and then after the preparation. Both PP and PPS results were assessed on 15 points of each tooth. The tooth was separated into three parts (incisal, middle and cervical) and then 5 points were randomly selected on the unprepared tooth and the lapped over when the preparation had been completed. This in turn gave a 15-point assessment of the amount of tissue removed. The data of the difference found was then opened in 3D scanning software called Magics( Materialise NV, Belgium) and was placed in the origin point after checking the x,y,z plains. Results: PP results showed a mean value in the Incisal of 0.328 +0.045mm, Middle results of 0.375 +0.097mm and Cervical results of 0.471 +0.07mm. PPS results showed mean values in the Incisal of 0.323 +0.056mm, Middle results of 0.403 +0.083mm and Cervical results of 0.462 +0.075mm. Conclusion: The results show no significant difference between the two groups. Therefore these results suggests that a PP or a PPS can both achieve the same precision in there preparation using a depth guide bur. Key Words: Ceramic veneer, 3D scanning, depth guide bur.
Keywords: Diş ve diş eti hastalıkları; Prostodonti; Tedavi